Pengaruh Kualitas Produk dan Strategi Pemasaran Syariah Terhadap Keputusan Pembelian Produk Abon Ayam Arofah - Ernawati, Erni; Al Farisi, Muhammad Salman; Herawati, Ermi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study examines the influence of product quality and sharia marketing strategy on purchasing decisions for Abon Ayam Arofah. Product quality includes taste, halal certification, safety, and consistency, while sharia marketing emphasizes honesty and transparency. Using a quantitative method and multiple linear regression analysis on 75 respondents, findings reveal that both variables significantly impact purchasing decisions. Product quality plays a more dominant role than sharia marketing, but both complement each other in building consumer trust. This study highlights that integrating high product quality with an effective sharia marketing strategy enhances competitiveness and consumer loyalty toward sharia-based products.